THE EFFECT OF REGIONAL INCOME ON REGIONAL EXPENDITURES IN GERBANGKERTOSUSILA - Marthaza Sabrina; Tituk Diah Widajantie (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to examine and prove the effect of regional retribution, the results of separated regional wealth management, other legitimate regional original revenues, and balancing funds for regional expenditures in Gerbangkertosusila. This type of research is quantitative research. The population and sample of this study are the Regional Government Budget Realization Reports in the Gerbangketosusila Area which consists of Gresik, Mojokerto, Surabaya, Sidoarjo, and Lamongan for 2017-2021. The data analysis technique used is panel data regression model analysis and hypothesis testing with the t test, f test, and the coefficient of determination. The results of this study indicate that partially the results of separated regional wealth management and balance funds has a significant positive effect on regional expenditures, while regional retribution and other legitimate regional original income has an insignificant positive effect on regional expenditures. Simultaneously, regional retribution, the results of separated regional wealth management, other legitimate PAD, and balance funds has a significant positive effect on regional spending.